2019
DOI: 10.1016/j.jsxm.2019.09.003
|View full text |Cite|
|
Sign up to set email alerts
|

Prevalence of Sexual Dysfunctions in Transgender Persons: Results from the ENIGI Follow-Up Study

Abstract: Introduction Studies about sexual functioning in trans persons have mainly focused on sexual functioning after genital gender-affirming surgery, have had small sample sizes, and have not explored the broad range of possible sexual dysfunctions. Measuring sexual functioning in trans persons during transitioning is important to determine the kind of care trans persons may need in order to regain their sexual health. Aim The fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
88
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(91 citation statements)
references
References 19 publications
2
88
0
1
Order By: Relevance
“…TW sex workers have a higher sexual frequency with more sexual partnerships, which could decrease the chance of CPS (in addition to a greater chance of suffering police and street violence, which can act as confounding variables) [ 63 , 64 ]. Sexual abstinence (e.g., case of transgender people who do not have sex due to sexual dysfunctions or other such as surgery complications, pain, and high body shame) also could lead to lower CPS [ 47 , 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…TW sex workers have a higher sexual frequency with more sexual partnerships, which could decrease the chance of CPS (in addition to a greater chance of suffering police and street violence, which can act as confounding variables) [ 63 , 64 ]. Sexual abstinence (e.g., case of transgender people who do not have sex due to sexual dysfunctions or other such as surgery complications, pain, and high body shame) also could lead to lower CPS [ 47 , 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…Die Ergebnisse dieser Studie haben jedoch einen ande- Stichproben (z. B. Cerwenka et al 2014;Kerckhof et al 2019), scheint darin zu liegen, dass Geschlechtsdysphorie und individuell empfundene Geschlechtsinkongruenz einen deutlich geringeren Stellenwert einnehmen. Tatsächlich erleben sich die TN mit den transitionsbedingten Körperveränderungen mehrheitlich als geschlechtskongruent.…”
Section: Individuelle Sexualitätunclassified
“…Supporting these results, a study 13 conducted with 518 transsexual people, of which 211 were trans men, showed that 54% of the men had sexual dysfunctions such as difficulty in achieving orgasm, pain during intercourse and decreased interest in sex. in the same study, 69% of the trans women had sexual problems such as pain during sex and decrease in sex drive 13 .…”
Section: Discussionmentioning
confidence: 85%